A virtual surgical telesimulation in micrographic dermatologic surgery (MOHS) (2003)
The development and propagation of surgical procedures in dermatology establish a need for an approach to a new way of teaching and supporting techniques which use emergent technologies. Our work is based upon a generic concept of software architecture for telemedicine applications, which could provide educational telesimulation in the dermatologic surgery technique known as Mohs micrographic surgery. This technique is used in the neoplasia resection treatment. Actually, the modules proposed are evolving in the Internet platform and are planned to interact in a cyclic manner from a diagnostic precision aid, through a planning surgical tool, to a simulator facility.